Experimental determination of L X-ray fluorescence cross sections for elements with 45 < Z < 50 at 10 keV - Edgardo Bonzi; Gabriela Grad; Raúl Barrea (Papers in Physics, 2014)
Synchrotron radiation at 10 keV was used to experimentally determine the Ll, L, LI, LII, LI and LII fluorescence cross sections for elements with 45 < Z < 50, as part of an ongoing investigation at low energies. The measured data were compared with calculated values obtained using coefficients from Scofield, Krause and Puri et al.